Formation of wormholes by dark matter in the galaxy Dragonfly 44 - Islam, Sayeedul; Rahaman, Farook; Övgün, Ali; Halilsoy, Mustafa (Canadian Science Publishing, Nrc Research Press, 2019)
Recently, the ultra-diffuse galaxy (UDG) Dragonfly 44 in the Coma Cluster was observed and observations of the rotational speed suggest that its mass is almost the same as the mass of the Milky Way. On the other hand, interestingly, the galaxy emits only 1% of the light emitted by the Milky Way. Thus, astronomers reported that Dragonfly 44 may be made almost entirely of dark matter. In this study we try to determine whether or not the dark matter that constitutes Dragonfly 44 can form a wormhole. Two possible dark matter profiles are used, namely, UDG King's model and generalized Navarro-Frenk-White (NFW) dark matter profile. We have shown that King's model dark matter profile does not manage to provide a wormhole whereas the generalized NFW dark matter profile manages to find wormholes.
Keywords: wormhole; dark matter; ultra-diffuse galaxy; Dragonfly 44; NFW dark matter profile